Heat Treatment in an Alloy Al64Cu27Fe15 - Nascimento, Luciano (Orbital: The Electronic Journal of Chemistry, 2020)
Aluminum-based alloys containing quasicrystalline phases have good wear resistance due to their low wear coefficient and high hardness. The formation of quasicrystalline phases depends on the composition of the alloy and the imposition of high cooling rates on the molten metal. In the raw state of fusion, presenting β-Al2Fe5(Cu) monoclinic phases, they are present together with the quasicrystalline phase-ω. A careful chemical composition control and an efficient heat treatment are necessary to obtain quasicrystalline phases. The objective of this work was to study the heat treatment in the homogenization of the quasicrystalline alloy Al64Cu27Fe15 obtained by smelting, in a controlled atmosphere. To understand the microstructural evolution, characterizations were made using SEM and XRD. The thermal treatment carried out for 24 hours, to obtain a microstructure with icosahedral phase coexisting with small increases in existing crystalline phases.DOI: http://dx.doi.org/10.17807/orbital.v12i4.1581